2022
DOI: 10.1002/dmrr.3591
|View full text |Cite
|
Sign up to set email alerts
|

Exercise modalities for type 2 diabetes: A systematic review and network meta‐analysis of randomized trials

Abstract: Aims:We aimed to determine the effects of different exercise modalities in patients with type 2 diabetes mellitus (T2DM). Methods:We searched PubMed, Embase, and the Cochrane Library from their inception until July 2020 to identify randomised controlled trials (RCTs) on exercise in adults with T2DM. Paired reviewers independently performed study selection, data extraction, and risk of bias assessment. The certainty of the evidence was assessed using the Confidence in Network Meta-Analysis (CINeMA) framework.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
2
7
0
1
Order By: Relevance
“…They found that flexibility exercise was the most effective exercise for reducing fasting glucose (–1.48 [–2.17 to –0.78] mmol/L) and HbA1c (–0.71 [–1.08 to –0.34] %) in T2DM patients, while only 2 studies were included to support this finding. 20 However, our results on aerobic exercise, resistance exercise, and combined exercise were in line with existing meta-analyses indicating that combined exercise was superior than performing each mode alone. 18,19 Our findings regarding aerobic interval vs continuous exercise on HbA1c were also consistent with a previous pairwise meta-analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They found that flexibility exercise was the most effective exercise for reducing fasting glucose (–1.48 [–2.17 to –0.78] mmol/L) and HbA1c (–0.71 [–1.08 to –0.34] %) in T2DM patients, while only 2 studies were included to support this finding. 20 However, our results on aerobic exercise, resistance exercise, and combined exercise were in line with existing meta-analyses indicating that combined exercise was superior than performing each mode alone. 18,19 Our findings regarding aerobic interval vs continuous exercise on HbA1c were also consistent with a previous pairwise meta-analysis.…”
Section: Discussionsupporting
confidence: 91%
“…We found that combined exercise (i.e., exercise training comprising several types of exercise, mainly aerobic + resistance) and aerobic interval exercise might be the most effective exercise modalities for prediabetes and T2DM, respectively. Several meta-analyses have been conducted to investigate the best exercise modality, 1820 while the classification of exercise modality in those studies differed from ours, leading to the inconsistency of the results. For example, one recent network meta-analysis categorized exercise into eight modalities (i.e., supervised aerobic, unsupervised aerobic, anaerobic, balance, supervised resistance, unsupervised resistance, combined aerobic and resistance, and flexibility exercise).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several RCTs have investigated whether exercise interventions (up to 96 weeks), involving either aerobic or resistance training alone, or in combination, can improve markers of metabolic health in older adults with T2DM [165][166][167][168][169][170]. Overall, these studies provide evidence that in those with T2DM, both supervised aerobic and resistance training are effective for improving HbA1c and fasting blood glucose levels [171]. In a RCT of 100 adults aged ≥55 years with T2DM, the effects of three different 16-week exercise interventions (aerobic exercise, resistance exercise, or a combination of both [same intensity but half the volume of other exercise groups]) on various metabolic health markers were compared with a control group encouraged to perform low-to-moderate intensity aerobic activities (e.g., brisk walking, cycling) for 150 minutes per week [165].…”
Section: Exercisementioning
confidence: 99%
“…However, medications usually have several side effects, may be ineffective, and can further exacerbate the disease, leading to JIA joint damage or even irreversible disability [ 11 ]. Exercise is a physical activity that maintains or enhances physical health and is characterized by a variety of forms, a broad audience, few side effects, and high operability, and is widely used in various disease areas such as obesity, cardiovascular disease, chronic obstructive pulmonary disease, diabetes, osteoporosis, cancer, and low back pain [ 12 16 ]. In children with JIA, the muscles around the affected joints are usually wasted, leading to low bone density and, consequently, to osteoporosis in adulthood [ 17 ].…”
Section: Introductionmentioning
confidence: 99%